Evaluation of Corneal Endothelial Cells after Transepithelial Photorefractive Keratectomy with Mitomycin-C Application - درويش تيم; يوسف حبيب; زيدان ياسمين (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To evaluate corneal endothelial cells density and morphology after transepithelial photorefractive keratectomy (tPRK) with Mitomycine-c (MMC) in low to moderate myopic patients. Methods: In this prospective study 112 eyes of 58 myopic patients underwent transepithelial photorefractive keratectomy followed by 0.02% MMC applied for 15 seconds using a methylcellulose sponge, in the ophthalmology department in Tishreen university hospital. endothelial specular microscope was performed in 112 eyes before, after 1, 3, and 6 months after surgery. Parameters studied included endothelial cell density (CD), coefficient of variation (CV) in cell area, and percentage of hexagonality (EX). Results: Mean endothelial cell densities before and after six months were 2898.79±338.68 and 2841.32±372.21, respectively (p=0.06). Mean coefficient of variation before and after surgery were 33.02±4.9 and 33.08±4.8, respectively (p=0.4). Mean percentage of hexagonal cells before and after surgery were 55.12±8.2 and 55.02±8.1 (p=0.09), respectively. Conclusion: Transepithelial photorefractive keratectomy with MMC 0.02% for 15 seconds did not have a significant effect on corneal endothelial cells density or morphology in this study.